2007
DOI: 10.1063/1.2437450
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Fluids Life Tests — Theory

Abstract: There are a number of different applications that could use heat pipes or loop heat pipes (LHPs) in the intermediate temperature range of 450 to 750 K, including space nuclear power system radiators, and high temperature electronics cooling. Potential working fluids include organic fluids, elements, and halides, with halides being the least understood, with only a few life tests conducted. Potential envelope materials for halide working fluids include pure aluminum, aluminum alloys, commercially pure (CP) tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Saaski and Owzarsky (1977) proposed an electrochemical method to predict the compatibility of halide working fluids with envelope materials. Tarau, Sarraf, Locci and Anderson (2007) found that this procedure had good agreement with the halide life tests discussed above.…”
Section: Halidesmentioning
confidence: 65%
See 3 more Smart Citations
“…Saaski and Owzarsky (1977) proposed an electrochemical method to predict the compatibility of halide working fluids with envelope materials. Tarau, Sarraf, Locci and Anderson (2007) found that this procedure had good agreement with the halide life tests discussed above.…”
Section: Halidesmentioning
confidence: 65%
“…(Saaski 1977(Saaski , 1980) Diphenyl/Black Iron 523 K (250°C)/7,158 hrs (Kenney, 1978) Diphenyl/Stainless Steel Cycle 598 K to 653 K (325°C to 380°C)/5,520 hrs./ 316 SS (Grzyll, 1991(Grzyll, , 1994(Grzyll, , 1995 623 K (350°C)/ 5,520 hrs./316 SS (Grzyll, 1991(Grzyll, , 1994(Grzyll, , 1995 548 K (275°C)/6,174 hrs/304 SS (Kenney, 1978) 543 K (270°C)/~9,000 hrs./316L SS (Groll, 1982(Groll, , 1987(Groll, , 1989 Short Term 673 K (400°C)/1200 hrs./304 SS (Kenney/ Feldman) 748 K (475°C)/72 hrs./304 SS (Kenney, 1978) 738 K (465°C)/100 hrs./304 SS (Kenney, 1978) 695 K (422°C)/366 hrs./304 SS (Kenney, 1978) 673 K(400°C)/~9,000 hrs./316L SS (Groll, 1982(Groll, , 1987(Groll, , 1989 Diphenyl Oxide/ Stainless Steel Short Term 573 K (300°C)/3200 hrs./347 SS & 304 SS (LASL, 1968a(LASL, , 1968b(LASL, , 1970 Dowtherm A/Mild Steel 543 K (270°C)/~40,000 hrs/ST 35 (Groll, 1982(Groll, , 1987(Groll, , 1989 523 K (250°C)/8383 hrs. (Kenney, 1978) 573 K (300°C) /~40000 hrs./ST 35 (Groll, 1982(Groll, , 1987(Groll, , 1989 Dowtherm A/ Stainless Steel 573 K (300°C)/~40,000 hrs/321 SS (Groll, 1982(Groll, , 1987(Groll, , 1989 541 K (268°C)/24,500 hrs/304 SS (Kenney, 1978) Short Term 673 K (400°C)/1,200 hrs (Kenney, 1978) 618 K (345°C)/1,000 hrs./304 SS (Anderson et al, 2007) 723 K (450°C)/180 hrs./304 SS…”
Section: B Organic Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium (Anderson, Dussinger, and Sarraf, 2006) Potassium (Lundberg, 1984;Sena and Merrigan, 1990) Cesium (Dussinger, Anderson, and Sunada, 2005) Titanium Tetrachloride (Tarau et al, 2007) Titanium Tetrabromide Naphthalene (GroU, 1989 ;Vasil'ev et al, 1988) Dowtherm A (Heine, Groll, andBrost, 1984;GroU, 1989) Toluene (Heine, Groll, andBrost, 1984;Groll, 1989) Water (Heine, Groll, and Brost, 1984;Groll, 1989;Antoniak et al, 1991;Anderson, Dussinger, and Sarraf, 2006) Ammonia (Ishizuka, Sasaki, and Miyazaki, 1985) Nitrogen (Swanson et al, 1995) and in Loop Heat Pipes with cesium (Anderson, Dussinger, and Sarraf, 2006), and ammonia (Ku et al, 2005).…”
Section: Titaniumavater Compatibilitymentioning
confidence: 99%